SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS FOR ENSURING THE SPIRALING DEVELOPMENT OF GRAMMAR AND VOCABULARY MATERIALS IN ENGLISH LANGUAGE TEXTBOOKS - Mukhamedova Muhlisa Avazjon kizi (Modern American Journals, 2025)
The study examines the scientific and methodological foundations necessary for ensuring the spiraling development of grammar and vocabulary materials in English language textbooks. Spiraling is understood as a linguodidactic approach in which linguistic elements are introduced at a basic level and revisited repeatedly in increasingly complex forms to support long-term acquisition. The research evaluates how spiraling contributes to cumulative learning, reinforces retention, and accommodates cognitive progression across educational stages. The study analyzes theoretical perspectives from linguistics, psycholinguistics, and pedagogy, and explores practical design strategies for embedding spiraling progression into textbook structure. Special emphasis is placed on vertical curriculum alignment, graded linguistic input, contextualized practice, and task-based reinforcement. The results show that effective spiraling enhances linguistic accuracy, fluency, and communicative competence by enabling learners to internalize grammar and vocabulary through structured recurrence. The study concludes that a scientifically grounded spiraling model is essential for creating coherent, developmentally appropriate, and methodologically consistent English language textbooks.
Keywords: Spiraling development, grammar progression, vocabulary acquisition, English language textbooks, linguodidactics, graded input,